Hubungan Antara Motivasi Kerja Dengan Kinerja Petugas Rekam Medis Di Rumah Sakit Nur Hidayah Bantul - Vanny Fadilla Rofika Arisita; Ristiana Eka Ariningtyas; Endang Purwanti (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Background: Motivation is an important factor that can affect employee performance. If the employee feel satisfied with their work, the employee will produce good performance, and vice versa. Based on the result of the preliminary study with the head of the medical record unit, it is known that they never get a reward if they work well, In addition there are still many officer who come late and performance of officers is still not paid attention. This condition resulted in work performed by medical recorders at Nur Hidayah Bantul hospital is not optimal, so it will affect work motivation. Objective: To determine the relationship between work motivation and the performance of medical recorder in the Nur Hidayah Bantul Hospital Method: This is a quantitative research with cross sectional design. The data collection technique used total sampling with a total respondent of 16 medical recorder. Results: From the results of the study, the results of work motivation showed that most medical recorder had sufficient work motivation (63%) and the performance of medical recorder mostly had sufficient performance (81%). From the results of the Spearman’s rho test on the relationship between work motivation and the performance of medical recorder in the Nur Hidayah Bantul hospital obtained r value 0.522 and p value 0.38 which means that there is a significant relationship between work motivation and performance. Conclusion: There is a relationship between work motivation and the performance of medical recorder in the Nur Hidayah Bantul hospital.